Interlaminar shear fracture healing of thermoset CFRP composite using multiphase thermoplastic healing agents. (1st January 2022) - Jony, Bodiuzzaman; Mulani, Sameer B.; Roy, Samit
Abstract: The shear fracture toughness (Mode II) recovery of damaged thermoset carbon fiber reinforced polymer (CFRP) composite by multiphase thermoplastic healing agents is presented here. Bio-mimetic heat-activated intrinsic healing was employed to recover the shear fracture toughness of fractured CFRP specimens. The activation of embedded shape memory polymers (SMP) closes the gap between the delaminated faces. Simultaneously, molten thermoplastic polycaprolactone (PCL) healants repair the micro or macro cracks. End notch flexure (ENF) test specimens were fractured in a quasi-static test to verify the proof-of-concept healing under Mode II shear loading. Rapid melting of PCL healants at ∼80 °C enabled the recovery of the damage site, while subsequent solidification recovered the structural integrity. The healing efficiency was quantified by comparing the shear fracture toughness ( G IIc ) of a healed specimen to the similar toughness of a virgin specimen. Maximum 88.39 ± 16.41 % recovery of virgin toughness was observed during the first heal cycles, and the healing efficiency was always greater than 70 % in all subsequent cycles. The fractographic features of the delaminated surfaces were observed and analyzed by scanning electron microscope (SEM) and optical microscope. The fractographic observation elucidated the mechanisms behind the shear toughness recovery in different healing cycles.